Shelf Life Extending Packaging, Inventory Control and Grocery Retailing. Issue 7 (1st March 2017) - Li, Qing; Yu, Peiwen; Wu, Xiaoli
Abstract : Retailers of perishable goods are often faced with the choice between more expensive packaging that can extend shelf life of their products and less expensive packaging that cannot. Different choices will lead to different sales, costs, and waste, and different choices require different inventory control policies. In this paper, we study the coordination of inventory and packaging decisions in a retailing environment. Items in an active package have a longer lifetime than those in a regular package and cost more. Customers always pick items with a longer lifetime first. When items with a longer lifetime are out of stock, a portion of customers are willing to buy less fresh items as substitutes. Our study shows the optimality of a "separation" policy when the substitution rate is high. In the separation policy, as the initial inventory level increases, the optimal policy changes from using active packaging only, then to using regular packaging only, and finally to ordering nothing. These results are very specific to the way perishable inventories are depleted in retailing. Our numerical study shows that although it may not be optimal in terms of cost, the adoption of active packaging can consistently achieve substantial waste reduction.